Strategi Pengembangan Bisnis Pada UMKM Makanan Sehat Warung Lotek Ibu Cucu - Wijaya, Fanji; Nurpatimah, Siti (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
This research was conducted using a qualitative method, which was prepared using SWOT analysis to find out what strategies are appropriate for developing the MSME business of the mother and grandson's look stall, especially with the existence of the same business, which could be a threat. Based on the research results using SWOT analysis, an overview of the position of Ibu Cucu's Lotek stall is in position IV, which means that Ibu Cucu's Lotek stall business is currently in a stable condition. To develop the Ibu Cucu Lotek stall business, after the analysis has been carried out and several known problems and the current position of the business is stable, the author suggests creating a new strategy for the MSME business actors of the Ibu Cucu Lotek stall to add employees so that it is not too burdensome when providing services to consumers and consumers as well. don't wait long when making a purchase. Then, for marketing, the author suggests registering your business on online platforms such as Gofood and Shopeefood to expand marketing and reach consumers further to find out about the products being sold. As technology develops at this time in the future, the author suggests providing payment via QRIS, Gopay, Dana, and Spay to make payments more manageable